2021
DOI: 10.3892/ijmm.2021.5005
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin induces autophagy through the inactivation of the ROS‑mediated Akt/mTOR signaling pathway in endometrial cancer

Abstract: Endometrial cancer (EC) is widely known as an aggressive malignancy. Due to the limited therapeutic options and poor prognosis of patients with advanced-stage EC, there is a need to identify effective alternative treatments. Chrysin is a naturally active flavonoid (5,7-dihydroxyflavone), which has been demonstrated to exert anticancer effects and may present a novel strategy for EC treatment. However, the role of chrysin in EC remains largely unclear. The aim of the present study was to examine the anticancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…However, our work did not focus on intercellular Ca 2+ in autophagy or the associated signaling pathways. An abundance of data indicates that the PI3K/Akt/mTOR, ERK1/2 and β-catenin signaling pathways are closely related to proliferation, apoptosis and autophagy [70] , [71] , [72] . In addition, extensive studies have reported that accumulating ROS inhibits the PI3K/Akt/mTOR, ERK1/2 and β-catenin pathways, leading to autophagy and apoptosis [36] , [37] , [73] .…”
Section: Discussionmentioning
confidence: 99%
“…However, our work did not focus on intercellular Ca 2+ in autophagy or the associated signaling pathways. An abundance of data indicates that the PI3K/Akt/mTOR, ERK1/2 and β-catenin signaling pathways are closely related to proliferation, apoptosis and autophagy [70] , [71] , [72] . In addition, extensive studies have reported that accumulating ROS inhibits the PI3K/Akt/mTOR, ERK1/2 and β-catenin pathways, leading to autophagy and apoptosis [36] , [37] , [73] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HO-1 and NQO-1 proteins in MAC-T cells were elevated after S. lutetiensis infection. Recent research demonstrated that NAC could block ROS production and further reversed LC3 II accumulation which triggered by coenzyme Q 0 , and the same mechanism of NAC also occurred in chrysin-induced autophagy [ 50 , 51 ]. We used NAC, an efficient ROS inhibitor [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that chrysin exerts its anti-cancer effects on endometrial cancer, gastric cancer, breast, lung, cervical, bladder, breast cancer, and colorectal cancer, etc. via selectively inhibiting various cell signaling pathways, such as: Akt/mTOR, JNK1/2, ERK1/2, NF-κB, etc., and promoting tumor cells apoptosis and autophagy ( Xia et al, 2015a ; Xia et al, 2015b ; Roy et al, 2019 ; He et al, 2021 ). However, the regulatory relationship between chrysin and m6A enzyme has not been reported.…”
Section: Part 3: the Anti-cancer Effect Of Nature Products By Regulat...mentioning
confidence: 99%